The effects of dietary bee pollen on lipid peroxidation and fatty acids composition of Japanese quails (Coturnix coturnix japonica) meat under different stocking densities - Seven, Pinar Tatli; Arslan, Aslihan Sur; Seven, Ismail; Gokce, Zehra (Taylor & Francis Ltd, 2016)
The objective of this study was to investigate the effects of supplementation of bee pollen (1g/kg) to the basal diet on lipid peroxidation and the fatty acids composition of Japanese quails under different stocking densities. Hundred and sixty Japanese quails were divided into 3 treatment groups each with four replicates consisting of 8 birds in control group and 16 birds in the other groups. Experimental groups were arranged as Control (160cm(2)/quail without supplementation), high stocking density (HSD) (80cm(2)/quail without supplementation), and POL (80 cm(2)/quail and 1g/kg bee pollen). Plasma Malondialdehyde level in the HSD group was significantly higher than those of Control and POL groups (P<.01). The catalase activity in blood of Control and POL groups was significantly higher than those of the HSD group(P<.01). In the HSD group the total polyunsaturated fatty acid (PUFA) ratio was lowered in all tissues. Increased PUFA ratios were observed in breast muscle and kidney tissue (P <.001), leg muscle (P<.05) and liver (P<.01) tissue in pollen-supplemented quails compared with the other groups. The n-6 PUFA ratio of breast muscle, kidney tissue (P<.001) and liver tissue (P<.01) was higher in the POL group than the other groups. As a result, the present study suggests that bee pollen supplementation to 1g/kg diet had potential protective activity on lipid peroxidation and tissue fatty acid composition of quails reared under HSD. In all groups, the bee pollen consumption increased PUFA levels in tissues, especially n-6 PUFA.
Keywords: Quail; stocking density; lipid peroxidation; fatty acids; bee pollen